2000
DOI: 10.1111/j.1553-2712.2000.tb02235.x
|View full text |Cite|
|
Sign up to set email alerts
|

The Emergency Department as a Potential Site for Smoking Cessation Intervention: A Randomized, Controlled Trial

Abstract: Abstract. Objective: To assess the effect of physician counseling and referral on smoking cessation rates and attendance at a smoking cessation program. Methods: This was a prospective, randomized clinical trial set in a suburban, community teaching hospital emergency department (ED). During study hours, dedicated research associates enrolled consecutive, stable, oriented patients who were smokers. Eligible, consenting patients were randomized to one of two intervention groups. The control group received a two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 19 publications
8
47
0
Order By: Relevance
“…This was expected, since the interventions were brief and patients were enrolled regardless of baseline motivation to quit. Such a pattern is characteristic of brief interventions in opportunistic settings [13,14] and consistent with the two published randomized trials in the ED setting [18,28]. Small effect sizes should not be viewed as evidence of non-viability.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This was expected, since the interventions were brief and patients were enrolled regardless of baseline motivation to quit. Such a pattern is characteristic of brief interventions in opportunistic settings [13,14] and consistent with the two published randomized trials in the ED setting [18,28]. Small effect sizes should not be viewed as evidence of non-viability.…”
Section: Discussionsupporting
confidence: 61%
“…However, they may not be particularly effective. A small pilot study of 152 patients by Richman et al [18] found that brief, scripted physician counseling did not lead to significantly higher cessation than a standard referral to a tobacco clinic alone. Moreover, research with alcohol suggests that there may be a trade-off between efficiency and efficacy.…”
Section: Follow-up Carementioning
confidence: 97%
“…Although the rate of uptake and utilization of the proactive quitline service in this trial appears to be superior relative to other strategies (Ockene et al, 1992;Richman et al, 2000;Winickoff, Hillis et al, 2003), 26% of referred patients did not receive a postdischarge call from the quitline. As part of the intervention protocol, preoperative nursing staff estimated the discharge date of patients, which was used by the quitline as a commencement date for patient contact.…”
Section: Discussionmentioning
confidence: 57%
“…The results also suggest that direct referral of patients to a proactive quitline service represents a more successful method of ensuring the provision of postdischarge support to smokers than other strategies such as referral to group support programs, primary care physicians, or free reactive telephone support services (Ockene et al, 1992;Richman et al, 2000;Winickoff, Hillis et al, 2003).…”
Section: Discussionmentioning
confidence: 91%
“…The ED is considered an appropriate setting for screening and counseling of tobacco usage by both public health and emergency medicine experts [6,7]. In spite of these opinions, in the two trials about smoking cessation counseling in EDs to date, neither was effective in decreasing smoking at a mean of 3-6 months [8,9].…”
Section: Introductionmentioning
confidence: 99%